Chronic Pelvic Pain and Quality of Life in Women with and without Endometriosis. Issue 1 (January 2013) - Centini, Gabriele; Lazzeri, Lucia; Dores, Daniela; Pianigiani, Luca; Iannone, Piergiorgio; Luisi, Stefano; Petraglia, Felice; Zupi, Errico
Purpose: To determine the impact of chronic pelvic pain on quality of life in women with or without endometriosis Methods: A total of 162 women with chronic pelvic pain were enrolled in a cross-sectional study and divided into two groups: 84 with endometriosis, 78 without endometriosis. Assessment of dysmenorrhea, non -menstrual pain, dyspareunia and diffuse abdominal pain by a visual analog scale, assessment of quality of life by SF-36. Results: The endometriosis group showed more dysmenorrhea but less dyspareunia and non-menstrual pain than women affected by other diseases. Pain had a negative influence on quality of life in both groups, but the endometriosis group showed a greater negative impact in all areas of SF-36, yet only in three (physical role, physical pain and mental role) was the difference statistically significant. Conclusions: Endometriosis impacts quality of life more than other forms of chronic pelvic pain. Interventions aimed at improving quality of life specifically designed for patients with chronic pelvic pain in general, and with endometriosis in particular, should be developed, tested, and integrated into the routine care regimen provided for these patients.